Lean manufacturing techniques implementation at Zest Venture Sdn Bhd - Nur Fakhriah, Mohd Noordin (2013)
Lean Manufacturing techniques has been widely implemented in industry. Lean manufacturing is a Japanese approach with a model and group of planned methods that is highlight eliminating non-value added activities (waste) while bringing quality products on time at least cost with greater effectiveness This research is about how to implement lean manufacturing techniques in the selected SME company which is Zest Venture Sdn Bhd with three objectives. The first objectives of this study is to propose relevant lean manufacturing techniques which could be applied in Zest Venture as to eliminate and reduce waste that existing in the production. The second objective is to identify and to eliminate non-value added in Zest Venture. Last but not least is to investigate and analyze production lead time and productivity in Zest Venture. The problem statement of this study is the attitude of the workers, lack of knowledge about lean manufacturing and time constraint in implementing lean manufacturing techniques in the company. In this study several methods were used which are trough observation, interview, survey, distribute questionnaire, time study and distance travel study. The techniques that are implemented in the company is 5S, Kaizen and Standard Operation Procedure (SOP). Results obtained from these studies demonstrate that the techniques of lean manufacturing can have a positive impact on the company since being able to reduce the wastage of time and space at the workplace by eliminating the non-value added activity in production line.